(untitled) (Emancipação, 2020)
The article discusses the existing convergences between Social Innovation and Emancipation. A systematic literature review was carried out in order to understand the motivations that lead to Social Innovation. In addition, some concrete cases of innovations in the literature reviewed have been described.